Glucosinolates of Lepidium graminifolium L. (Brassicaceae) from Croatia. Issue 3 (1st February 2021) - Montaut, Sabine; Read, Sharayah; Blažević, Ivica; Nuzillard, Jean-Marc; Harakat, Dominique; Rollin, Patrick
Abstract: The glucosinolate (GSL) profiles (inflorescence, stem, root, and fruit) of the wild-growing plant Lepidium graminifolium L. (Brassicaceae) from Croatia was established by LC-MS analysis. During this investigation, we confirmed the presence of benzyl- (1 ), 3-methoxybenzyl- (2 ), 4-hydroxybenzyl- (4 ), 4-methoxyindol-3-ylmethyl- (7 ) GSLs and reported for the first time in the plant the presence of (2  R )-hydroxybut-3-enyl- (11 ), (2 S )-hydroxybut-3-enyl- (12 ), but-3-enyl- (13 ), and 2-phenylethyl- (14 ) GSLs. Finally, 3-hydroxybenzyl GSL (3 ) was isolated for the first time from L. graminifolium inflorescence and characterised by spectroscopic data interpretation. Graphical Abstract: